Effects of complete home-based biofeedback therapy on insomnia disorders in patients with cancer - Hasuo, Hideaki; Mori, Keita; Matsuoka, Hiromichi; Shimazu, Mariko; Shizuma, Hisaharu; Morita, Yukihiro; Ishikawa, Hideki (Frontiers in Sleep, 2025)
BackgroundProfessional palliative care for patients with cancer focuses on symptom management.MethodsThis exploratory, randomized controlled study was conducted to compare the effects of complete home-based heart rate variability biofeedback (HRV-BFB) using an estimation formula for resonance frequency in managing insomnia disorders among patients with cancer.ResultsOnly 28 patients were included from the initial enrollment of 30 patients from two study sites. Results showed that compared to the control group, the HRV-BFB group improved sleep efficiency from 82.0% (standard deviation: 9.1%) to 87.8% (standard deviation: 7.2%) (p < 0.001) and decreased use of sleeping medication from 88.2% (95% confidence interval, 73.6–95.8) to 51.5% (95% confidence interval, 41.8–61.1) (p < 0.001).ConclusionsThis suggests that complete home-based HRV-BFB using an estimation formula for resonance frequency may be a promising tool for treating insomnia disorders in patients with cancer, potentially improving sleep efficiency and decreasing reliance on sleep medications.Clinical trial registrationUMIN 000046884. Registered February 11, 2022. https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000053496.